ANALISIS FISIOLOGI PERNAPASAN PADA KONDISI HIPERTENSI DAN ASMA - Annisa Triharta Ritonga; Alya Salsabila Nasution; M.Fahrizal Ramadhan; Haafizhah Husnah; Rini Andriyani; Fadila Susanri Pulungan; Irfan Sazali Nasution (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Abstract. This study aims to analyze respiratory physiology in patients with hypertension and asthma, as well as the pathophysiological interactions between these two diseases. An observational study was conducted on 200 patients consisting of 50 hypertension patients, 50 asthma patients, 50 patients with hypertension and asthma, and 50 healthy controls. Parameters measured include lung function (FEV1, FVC, PEFR), blood pressure, lung diffusion capacity, and systemic inflammatory biomarkers. The results showed that patients with hypertension experienced a 15% reduction in lung diffusion capacity compared to controls (p<0.01). Asthma patients showed a decrease in FEV1 and PEFR of 25% and 30% respectively (p<0.001). In the hypertension and asthma group, an additive effect was found with a more significant reduction in lung function (FEV1: -35%, PEFR: -40%, p<0.001) and an increase in systemic inflammatory biomarkers (CRP: +45%, p<0.01). Multivariate regression analysis showed a positive correlation between the severity of hypertension and decreased lung function in asthma patients (r=0.68, p<0.001). In conclusion, there is a significant pathophysiological interaction between hypertension and asthma that impacts respiratory physiology. These findings emphasize the importance of an integrated approach in the management of patients with both conditions.